Entrepreneurial Tendencies and Intentions of Students in a Rural-based Technical and Vocational Education and Training College - Moji D. Mathosa; Mamoloko F. Rachidi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
In an environment with unprecedented unemployment levels, entrepreneurship is promoted as an approach that has a potentially positive effect on the economy through innovation and employment creation. The objective of the current study was to determine entrepreneurial interest and intention among college students. This study examined the entrepreneurial tendencies of students registered for an entrepreneurship module in a college. The study was quantitative and used Caird’s General Enterprising Tendencies Questionnaire to collect information from students registered at the local college. The theory of planned behavior was utilized to explore whether, if the students have an interest in business, they are also inclined to act on that desire to participate in business undertakings. The results suggested that the students in the study possessed the tendency to be entrepreneurial and were keen to start businesses at some point in their lives. Yet, they mostly do not intend to start business ventures for several reasons, including fear of failure. The study contributes to the knowledge that underprivileged still contributes to a lack of entrepreneurial inclination, and support is paramount in nurturing that entrepreneurial interest. The study recommends that the college’s entrepreneurship education emphasizes information about reasonable small business prospects in the area; provide relevant information such as funding or registration, for the encouragement and advancement of especially youth-owned businesses; and host dialogues that should be delivered by young successful small business owners or managers.